On Elizabeth Bishop - Tóibín, Colm, 1955- (Book collections on Project MUSE., 2015)
In this book, novelist Colm Tóibín offers a deeply personal introduction to the work and life of one of his most important literary influences-the American poet Elizabeth Bishop. Ranging across her poetry, prose, letters, and biography, Tóibín creates a vivid picture of Bishop while also revealing how her work has helped shape his sensibility as a novelist and how her experiences of loss and exile resonate with his own. What emerges is a compelling double portrait that will intrigue readers interested in both Bishop and Tóibín. For Tóibín, the secret of Bishop's emotional power is in what she leaves unsaid. Exploring Bishop's famous attention to detail, Tóibín describes how Bishop is able to convey great emotion indirectly, through precise descriptions of particular settings, objects, and events. He examines how Bishop's attachment to the Nova Scotia of her childhood, despite her later life in Key West and Brazil, is related to her early loss of her parents-and how this connection finds echoes in Tóibín's life as an Irish writer who has lived in Barcelona, New York, and elsewhere. Beautifully written and skillfully blending biography, literary appreciation, and descriptions of Tóibín's travels to Bishop's Nova Scotia, Key West, and Brazil, On Elizabeth Bishop provides a fresh and memorable look at a beloved poet even as it gives us a window into the mind of one of today's most acclaimed novelists.